2006
DOI: 10.1007/s11894-006-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in the gastrointestinal tract

Abstract: Although we know that eosinophils reside in the normal gastrointestinal tract and increase during inflammatory states, their exact role in gut homeostasis and in the pathogenesis of inflammatory processes is not certain. An increasing number of clinical reports suggest that eosinophils participate in the pathogenesis of mucosal inflammation, and emerging literature is beginning to define these mechanisms. For example, homing of eosinophils to the gastrointestinal tract is better understood with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…A case report by Inamura et al [5] demonstrated the accumulation of mast cells in the colon interstitium after immunohistochemical staining for mast cell tryptase, which may suggest a possible pathogenic role of IgE. Specific eosinophil chemoattractants, such as interleukin-5 and eotaxins, may also have a pathogenic role in EC [6]. Hahn and Hornick [7] specifically evaluated mast cells in mucosal biopsies from patients with systemic mastocytosis and a group of patients with diverse inflammatory disorders.…”
Section: Etiologymentioning
confidence: 99%
“…A case report by Inamura et al [5] demonstrated the accumulation of mast cells in the colon interstitium after immunohistochemical staining for mast cell tryptase, which may suggest a possible pathogenic role of IgE. Specific eosinophil chemoattractants, such as interleukin-5 and eotaxins, may also have a pathogenic role in EC [6]. Hahn and Hornick [7] specifically evaluated mast cells in mucosal biopsies from patients with systemic mastocytosis and a group of patients with diverse inflammatory disorders.…”
Section: Etiologymentioning
confidence: 99%
“…In particular, the signalling pathways responsible for evoking migration of human eosinophils and their activation at the inflammatory focus are incompletely understood. Understanding of the mechanisms involved in eosinophil recruitment, activation and survival at sites of inflammation may be useful for the development of novel therapies to control diseases in which eosinophils play a pathophysiological role, such as bronchial asthma, inflammatory bowel diseases, atopic dermatitis and myocarditis [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of cytokines such as lymphotoxin and tumor necrosis factor (TNF) were reported to be included in this process. It is known that intestinal eosinophils play a role in several inflammatory conditions such as infections, hypersensitivity reactions, and several other chronic intestinal disorders [48,49]. Therefore, considering the large number of reports that emphasize the roles of inflammatory process involving mast cells in the pathophysiology of IBS [50][51][52], the pathologic findings mentioned above deserve to be studied sufficiently.…”
Section: Discussionmentioning
confidence: 99%